Prevention and control of hospital infection (Research, Society and Development, 2023)
This work aimed to review in the literature the description of the prevention and control of nosocomial infection. This is a bibliographic, narrative, exploratory and descriptive review study. The searches were carried out in the PubMed, SciELO and Web of Science databases, published in Portuguese and/or English, in the period between 2018 and 2022. The selection of studies was carried out by reading the title, abstract and full text. A total of 19 articles were selected for the final sample. The themes found were grouped into two major guiding axes: the first category highlights infection in the hospital environment. The second category presents infection prevention and control measures in the hospital environment. Nosocomial infection is a serious public health problem. Work overload, low adherence to disinfection practice and inadequate reuse of personal protective equipment are factors that facilitate the occurrence of nosocomial infections. However, there are infection prevention and control strategies in the hospital environment capable of minimizing the problem, such as hand hygiene, disinfection of materials and equipment, proper use of personal protective equipment, and notification of infection cases to the surveillance service.